Keluarga yang Sehat dan Kuat sebagai Profil Keluarga Kristiani - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Discreet: Journal Didache of Christian Education, 2021)
In building a house, a strong foundation is needed so that the house that is built is not easily collapsed, even sturdy and earthquake resistant. Likewise in building a family, if the foundation is not strong and healthy, then the family to be built will quickly be destroyed. A healthy and strong family has several characteristics that must be worked on from time to time in order to take root and grow healthier and stronger over time. Using the descriptive qualitative method with a literary approach, it can be concluded that a healthy and strong family is a family that is in accordance with God's original design, where initially the family is God's initiative as the first institution formed by God since the beginning of the creation period. As a result of sin, God's design is broken, the family is broken. The beautiful designs that Allah makes for the family are neglected, each one lives for self-centered interests so that family life becomes unhealthy and insecure and sometimes even some end up in separation. Abstrak Dalam membangun rumah diperlukan fondasi yang kuat agar rumah yang dibangun tidak gampang rubuh bahkan kokoh dan tahan gempa. Demikian juga halnya dalam membangun keluarga, jika fondasinya tidak kuat dan tidak sehat, maka keluarga yang akan dibangun akan cepat hancur. Keluarga yang sehat dan kuat memiliki beberapa ciri yang harus terus diusahakan dari waktu ke waktu agar berakar dan bertumbuh semakin sehat dan kuat seiring dengan perjalanan waktu. Menggunakan metode kulaitatif deskritif dengan pendekatan literature dapat disimpulkan bahwa keluarga yang sehat dan kuat merupakan keluarga yang sesuai dengan rancangan Allah semula yang mana awalnya keluarga adalah inisiatif Allah sebagai institusi pertama yang dibentuk Allah sejak awal masa penciptaan. Akibat dosa maka rancangan Allah rusak, keluarga berantakan. Rancangan indah yang dibuat Allah bagi keluarga diabaikan, masing-masing hidup untuk kepentingan berpusat pada diri sendiri sehingga kehidupan keluarga menjadi tidak sehat dan tidak kuat bahkan tidak jarang beberapa yang berakhir dengan perpisahan.